2020
DOI: 10.1155/2020/5476425
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Framework to Support the Delivery of Effective Pain Management for Children: An Exploratory Qualitative Study

Abstract: Two million children are admitted to hospital every year in the UK and between 59% and 94% will experience pain, with 27–40% of them experiencing moderate to severe pain. Currently, there are a number of well-researched guidelines on children’s pain available, yet pain prevalence is high. Despite the guidelines, there is a lack of an overall framework that includes the necessary components to deliver effective pain management. This study was built on previous work about key elements that support children’s pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…However, it has been previously shown that HCPs often rely on child and family advocacy before providing pain management [ 32 ], creating a mismatch between family expectations and HCP approach to pain care. It is well accepted that, after the patient themselves, parents (and other caregivers) are often most familiar with their child’s demeanour and can better identify deviations from baseline and the extent of their child’s pain and discomfort [ 33 , 34 ]; this would put them in an excellent position to advocate for (or with) their child. However, many participants, regardless of whether they had a positive or negative pain experience, noted that they were either too intimidated by HCPs to advocate for pain care or were dismissed when asking for additional pain management options.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been previously shown that HCPs often rely on child and family advocacy before providing pain management [ 32 ], creating a mismatch between family expectations and HCP approach to pain care. It is well accepted that, after the patient themselves, parents (and other caregivers) are often most familiar with their child’s demeanour and can better identify deviations from baseline and the extent of their child’s pain and discomfort [ 33 , 34 ]; this would put them in an excellent position to advocate for (or with) their child. However, many participants, regardless of whether they had a positive or negative pain experience, noted that they were either too intimidated by HCPs to advocate for pain care or were dismissed when asking for additional pain management options.…”
Section: Discussionmentioning
confidence: 99%
“…early healing/repairing training, according to the after a physical operation condition of the patient, a series of targeted healing training programs are given to help increase in a good way the blood circulation of the tissue around the crack, reduce its swelling response, and speed up the recovery process of the affected limb [36][37][38][39][40][41][42][43][44]. Online pain management, guidance, and supervision of early healing training for patients are needed, and use of repairing evaluations and patient diaries [45].…”
Section: Discussionmentioning
confidence: 99%
“…Developing a contextualised and individualised understanding of the child's pain is a requirement of generating optimum pain care (Simons et al, 2020) and requires the nurse to achieve child–parent involvement to collect data about the specific needs and concerns of the child and parent; this exchange generates a more complete picture of the child's pain (Carter et al, 2021). Such processes comprise a range of content, including nurses asking specific questions about the origin and nature of the child's pain and using age‐appropriate pain scales as a means of assessing pain objectively (Jordan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Children's and parents' involvement in pain management and active communication between children, parents, and nurses has been reported as a central tenet for effective pain care after surgery (Royal College of Nursing, 2009). Therefore, one of the reasons behind suboptimal paediatric postoperative pain management could be related to child–parent‐nurse relationships during this process as there are evidences that, in addition to incongruence in beliefs and practices, communication is also largely responsible for disparities in pain management (Bakir et al, 2022; Simons et al, 2020; Vasey et al, 2019). However, there has been less emphasis on this triad's relationships, which may have an impact on how postoperative pain is managed and on children's experience of pain.…”
Section: Introductionmentioning
confidence: 99%